Antibacterial Effects of Erbium Chromium Laser along with/without Silver Nanoparticles in Root Canals Infected by Enterococcus faecalis - Seyedeh Sareh Hendi; Negin Amiri; Banafsheh Poormoradi; Mohammad Yousef Alikhani; Saeid Afshar; Maryam Farhadian (International Journal of Dentistry)
This study investigates the antibacterial effects of erbium chromium laser at 2780 nm, silver nanoparticles, and erbium chromium along with silver nanoparticles on Enterococcus faecalis in comparison with sodium hypochlorite. In the present study, 90 extracted human single-rooted teeth were selected and standardized to a length of 15 mm. The canals were prepared by V-taper Gold rotary files and then incubated with E. faecalis for 21 days. The samples were divided into four experimental groups including hypochlorite sodium, silver nanoparticle, erbium chromium laser, and erbium chromium laser along with silver nanoparticle groups. Results showed that there was a significant reduction in colony count for all groups after interventions. Moreover, there was a significant reduction in the colony count for sodium hypochlorite group in comparison with another groups, and this group showed the highest reduction of colony count. There was a significant difference between silver nanoparticles and erbium chromium laser groups in colony count. According to the results, the silver nanoparticles offered strong antibacterial effects on E. faecalis and therefore can decrease bacterial colonies, while the use of the laser, despite the reduction of the bacterial colony, could not be sufficiently used for disinfection of root canal system.